The effect of BMP9 on inflammation in the early stage of pulpitis - Tianzhu SONG; Xiangfen LI; Liu LIU; Yanglin ZENG; Dongzhe SONG; Dingming HUANG (University of São Paulo, 2023)
Abstract Bone morphogenetic protein 9 (BMP9) tends to be associated with various inflammatory responses of diseases, but its relationship with pulpitis remains unknown. Objective This study aimed to evaluate the effects and mechanisms of BMP9 in pulpitis. Methodology A rat model of pulpitis was used to evaluate the expression of BMP9, which was also analysed in Porphyromonas gingivalis lipopolysaccharide (Pg-LPS)-stimulated human dental pulp cells (hDPCs). The effects and mechanism of BMP9 on the regulation of inflammatory factors and matrix metalloproteinase-2 (MMP2) were evaluated using real-time quantitative PCR, western blotting, and immunocytofluorescence. Moreover, the migration ability of THP-1 monocyte-macrophages, treated with inflammatory supernate inhibited by BMP9, was previously tested by a transwell migration assay. Finally, a direct rat pulp capping model was used to evaluate in vivo the influence of the overexpression of BMP9 in pulpitis. Results The expression of BMP9 decreased after 24 h and increased after 3 and 7 d in rat pulpitis and inflammatory hDPCs. The overexpression of BMP9 inhibited the gene expression of inflammatory factors (IL-6, IL-8, and CCL2) and the secretion of IL-6 and MMP2 in Pg-LPS-stimulated hDPCs. The level of phosphorylated Smad1/5 was upregulated and the levels of phosphorylated ERK and JNK were downregulated. The inflammatory supernate of hDPCs inhibited by BMP9 reduced the migration of THP-1 cells. In rat pulp capping models, overexpressed BMP9 could partially restrain the development of dental pulp inflammation. Conclusion This is the first study to confirm that BMP9 is involved in the occurrence and development of pulpitis and can partially inhibit its severity in the early stage. These findings provided a theoretical reference for future studies on the mechanism of pulpitis and application of bioactive molecules in vital pulp therapy.